2017
DOI: 10.24251/hicss.2017.601
|View full text |Cite
|
Sign up to set email alerts
|

Enforcing Information Security Protection: Risk Propensity and Self-Efficacy Perspectives

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Researchers have recognized risk propensity as an important antecedent to security threat perceptions and avoidance behaviors (Moody, Galletta, Walker, & Dunn, 2011;Nguyen & Kim, 2017;Sun & Ahluwalia, 2008;Vance et al, 2014). Nguyen and Kim (2017) studied the level of association between 244 university students' risk propensities and their information-avoidance behaviors. They found significant associations between individuals' risk propensities and their threat perceptions and behaviors.…”
Section: Risk Propensitymentioning
confidence: 99%
“…Researchers have recognized risk propensity as an important antecedent to security threat perceptions and avoidance behaviors (Moody, Galletta, Walker, & Dunn, 2011;Nguyen & Kim, 2017;Sun & Ahluwalia, 2008;Vance et al, 2014). Nguyen and Kim (2017) studied the level of association between 244 university students' risk propensities and their information-avoidance behaviors. They found significant associations between individuals' risk propensities and their threat perceptions and behaviors.…”
Section: Risk Propensitymentioning
confidence: 99%
“…Decisions related to IT threats inherently involve a combination of risks characterized by high ambiguity [12]. Therefore, it can be expected that there will be a relationship between an individual's risk propensity and threat perception or behavior [13]. In fact, many studies have shown that risk propensity has a significant impact on security threat perception and avoidance behavior [14,15].…”
Section: B Research Purposementioning
confidence: 99%